Asymmetric dimethylarginine as an independent risk marker for mortality in ambulatory patients with peripheral arterial disease - Böger, Rainer H.; Endres, H. G.; Schwedhelm, E.; Darius, H.; Atzler, D.; Lüneburg, N.; von Stritzky, B.; Maas, Renke; Thiem, U.; Benndorf, R. A.; Diehm, Curt (Journal of internal medicine, 2011)
Abstract. Böger RH, Endres HG, Schwedhelm E, Darius H, Atzler D, Lüneburg N, von Stritzky B, Maas R, Thiem U, Benndorf RA, Diehm C (Institute of Clinical Pharmacology and Toxicology, University Medical Center Hamburg-Eppendorf, Hamburg; Ruhr University Bochum; Vivantes Berlin-Neukölln Medical Center, Berlin; Sanofi-Aventis Pharma GmbH, Berlin; Institute of Clinical Pharmacology and Toxicology, University of Erlangen; Ruhr University Bochum, Herne; Klinikum Karlsbad-Langensteinbach, Affiliated Teaching Hospital of the Ruprecht-Karls-University of Heidelberg, Germany) Asymmetric dimethylarginine as an independent risk marker for mortality in ambulatory patients with peripheral arterial disease. J Intern Med 2010; 269: 349-361. Background. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide (NO) synthesis causing endothelial dysfunction, an early sign of atherogenesis. Symmetric dimethylarginine (SDMA) does not inhibit NO synthases. Peripheral arterial disease (PAD) is a systemic indication of atherosclerosis. Methods. We assessed the associations between both ADMA and SDMA blood levels and major cardiovascular and cerebrovascular events or death from any cause within a 5-year follow-up in the multicentre getABI trial. From a cohort of 6821 primary care patients, aged ≥65 years, all 1260 patients with prevalent PAD were compared with a random sample of 1187 non-PAD controls. A total of 11 544 patient-years were documented. Multivariate risks were calculated by Cox proportional hazard models, adjusting for PAD, renal dysfunction and other important cardiovascular risk factors. Results. We documented 390 deaths, 296 cardiovascular events and 98 cerebrovascular events. Increased ADMA levels in the 4th quartile were significantly associated with total mortality [hazard ratio (HR) 1.41; 95% CI 1.14-1.74] and with cardiovascular events (HR 1.32; 95% CI 1.03-1.69), but there was a nonsignificant association with cerebrovascular events (HR 1.50; 95% CI 0.98-2.29). Increased SDMA was only just significantly associated with mortality (HR 1.27; 95% CI 1.01-1.59). In PAD patients compared with non-PAD controls, only mean SDMA concentration was considerably increased (0.52 μmol L−1 vs. 0.48 μmol L−1; P < 0.001) mainly because of a highly significant association with impaired renal function. Conclusion. These data suggest that ADMA but not SDMA is an independent risk marker for death from any cause or from cardiovascular events. The association between SDMA and mortality is in part explained by a close link between SDMA and renal function.